A Content Analysis of Bonus Pack Promotions. (2nd November 2017) - Carlson, Jay
ABSTRACT: Bonus packs created by manufacturers have been characterized by scholars as special factory packs offering the consumer extra product for the same price or at no additional cost. However, this portrayal may fail to fully capture what consumers actually encounter in stores during and following a bonus pack promotion. Indeed, little is known about the types of products that manufacturers promote as bonus packs and how offers for them are specified, how retailers price them, and also what happens when the offers are discontinued. To address these shortcomings, a content analysis is conducted. The results illustrate a richness to bonus pack promotions that previous views of the topic have not described.